2009
DOI: 10.1158/1078-0432.ccr-08-2418
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Hepatitis C Virus core Gene Are Associated with Advanced Liver Disease and Hepatocellular Carcinoma

Abstract: Purpose Hepatitis C virus (HCV) infection can promote the development of hepatocellular carcinoma (HCC). Published data implicate the HCV core gene in oncogenesis. We tested the hypothesis that core gene sequences from HCC patients differ from those of patients without cirrhosis/HCC. Experimental Design Full-length HCV sequences from HCC patients and controls were obtained from the investigators and GenBank and compared to each other. A logistic regression model was developed to predict the HCC risk of indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 39 publications
2
66
0
2
Order By: Relevance
“…In addition to the poor virological responses of HCV core amino acid 70/91 mutants to peg-IFN-plus-RBV treatment (4,6,12), patients infected with the core mutants showed increased incidence of hepatocellular malignancies (2,15,49). It has been reported that the HCV core R70 but not L91 mutant frequently causes steatosis and increased hepatic oxidative stress (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the poor virological responses of HCV core amino acid 70/91 mutants to peg-IFN-plus-RBV treatment (4,6,12), patients infected with the core mutants showed increased incidence of hepatocellular malignancies (2,15,49). It has been reported that the HCV core R70 but not L91 mutant frequently causes steatosis and increased hepatic oxidative stress (52).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to viral factors, the relationship between the viral core region and disease progression in HCV genotype 1b infection has attracted clinical attention. Specifically, it has been reported that the core amino acid (aa) 70 residue, identified as a variable related to the outcome of interferon (IFN) therapy (3), is closely associated with the progression of hepatitis and hepatocarcinogenesis in Japan and North America (4)(5)(6)(7). Those previous studies and our own have reported that core aa 70 variation is strongly linked to carcinogenesis and that substitutions in the core aa 70 region aggravate hepatitis and heighten the risk of hepatocarcinogenesis during the clinical course, corroborating the relationship between the status of the core region and disease progression (8,9).…”
Section: H Epatitis C Virus (Hcv)-related Liver Disease Gradually Advmentioning
confidence: 99%
“…Mutations in the hepatitis C virus core gene are associated with advanced liver disease and hepatocellular carcinoma [42] . And there has been found an association between mutations in the core region of hepatitis C virus genotype 1 and hepatocellular carcinoma development [43] .…”
Section: Hepatitis C Virusmentioning
confidence: 99%